2020
DOI: 10.3390/en13123133
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on a Vapor Injection Heat Pump System with a Single-Stage Compressor

Abstract: In this study, a heat pump of 10 kW with vapor injection using refrigerant of R410A was developed. A vapor injection pipe connecting a gas–liquid separator at the outlet of the main expansion valve and the suction of a single-stage rotary compressor was designed. The heating performance of this vapor injection heat pump was investigated and analyzed at different compressor frequencies and primary temperatures. The experimental results show that for the heat pump without vapor injection, the heating capacity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The main advantage of this technique is the rise of the capacity by controlling the injected refrigerant mass flow rate 14 . Furthermore, it provides cooling to the compressor, decreasing the discharge temperature 15 and therefore, the operating envelope of the compressor can be expanded, compared to the standard vapour compression cycle. Additionally, the injection technique, especially with liquid refrigerant, decreases the oil temperature leading to better oil performance and reduces oil degradation effects 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of this technique is the rise of the capacity by controlling the injected refrigerant mass flow rate 14 . Furthermore, it provides cooling to the compressor, decreasing the discharge temperature 15 and therefore, the operating envelope of the compressor can be expanded, compared to the standard vapour compression cycle. Additionally, the injection technique, especially with liquid refrigerant, decreases the oil temperature leading to better oil performance and reduces oil degradation effects 16 .…”
Section: Introductionmentioning
confidence: 99%
“…From experiments, it is found that the new air-conditioning heat pump system can operate stably and efficiently with a coefficient of performance (COP) of 6.0. Liu et al [15] developed a vapor injection heat pump and investigated the performance of the heat pump under different driving frequencies of the compressor and primary temperatures. It was found that the heating capacity and heating performance of the heat pump can be increased and the discharging temperature of the compressor can be reduced by the vapor injection.…”
Section: Introductionmentioning
confidence: 99%